Meningkatkan Hasil Belajar Dan Bernalar Kritis Pakbp Melalui Model PBL Berbantuan Wayang Kardus Fase B Kelas IV - Kurniatisari Kurniatisari; FR. Wuriningsih; Budi Hartana (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Nowadays, Critical Thinking plays a significant role and totally needed because it is closely related to the improvement of Profile Pelajar Pancasila as one of the Indonesian educational goals. It helps students to understand and prefer to be a selective person in giving and taking information, and it also makes the students become wiser in taking a decision based on Pancasila values. In fact, it is still found that there are many elementary school students' critical thinking abilities are still low. The purpose in doing this research is in order to know the effect of the Problem Based Learning (PBL) method to assisted cardboard puppet learning media on the result of learning and critical thinking skills in the subject of Catholic Religious Education and Character (PAKBP) about "The Ten Commandments of God as a Guide to Life" for grade 4th students, Phase B at Panggung Lor Elementary School, Semarang City. The method used in this research is Classroom Action Research (CAR). The population in this research is 12 students grade IV at Panggung Lor Elementary School, Semarang City, in the 1st semester academic year of 2024-2025.In analyzing the data, the researcher used descriptive analysis. It includes the results of observations of students' critical thinking skill in the PAKBP learning process using the PBL method of assisted cardboard puppet learning media and test data result of students' learning.The results of observations of student activities are analyzed descriptively using percentage statistics. The results of the research show that the application of the Problem Based Learning (PBL) with the help of cardboard puppets can improve learning outcomes and critical thinking abilities of students in the subject of Catholic Religious Education and Character Class IV, Phase B at Panggung Lor State Elementary School, Semarang City.